Pembaharuan Pendidikan Islam: Dalam Pemikiran Mahmud Yunus - nasihuddin, muhammad (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
In the 20th century the situation of Islamic education in Indonesia in general is still traditional. The curriculum used in various Islamic educational institutions is still dichotomized between the science of religion and general science. The orientation of teaching still rests on the mastery of the material through the verbalistic all-round system of memorization. Ie able to say but do not understand the purpose, let alone practice it. In this study the authors focus on the discussion of how the concept of Islamic education by Mahmud Yunus, as a figure of formation of Islamic education. This can be seen from his thoughts in describing the purpose of education, curriculum, methods, teachers in Islamic education, in describing the goals of Islamic education, human noble and able to develop all the potential that exists within him. While in curriculum making, he implements an integrated curriculum, namely integrate science of religion and general science in Islamic educational institutions. The method of learning applied by Mahmud Yunus, not only tend to the lecture method, but he uses a variety of teaching methods and tailored to the subject matter so that the learning materials will be integrated. While the teacher expected by Mahmud Yunus is to emphasize that every teacher can live and live in the middle of the students, so communication between teachers and students can be done with affection.